Cardiometabolic profiles in children and adults with overweight and obesity and down syndrome. Issue 3 (20th December 2022) - Oreskovic, Nicolas M.; Baumer, Nicole T.; Di Camillo, Chiara; Cornachia, Michelle; Franklin, Catherine; Hart, Sarah J.; Kishnani, Priya S.; McCormick, Andrew; Milliken, Anna L.; Patsiogiannis, Vasiliki; Pawlowski, Katherine G.; Santoro, Stephanie L.; et al.
Abstract: Individuals with Down syndrome (DS) are at increased risk for being overweight/obese, but the associated cardiometabolic risk (CR) is not clear. Cross‐sectional anthropometric and clinical laboratory data from a multi‐site, international cohort of individuals with DS were analyzed to determine cardiometabolic risk by reporting observed distributions of cardiometabolic biomarkers in overweight/obese individuals with DS throughout the lifespan. Descriptive statistics and regression analyses by age categories determined the distributive percentiles for cardiometabolic biomarkers and tested for adiposity as a predictor of CR. Across seven DS clinics, data were collected on 240 patients between the ages of 3 and 63 years, with one quarter overweight and three quarters obese among children and nearly all adults being obese. In children and adults, most cardiometabolic biomarker profiles showed distributive values within normal ranges. Blood lipids were positively associated with body mass index (BMI) in children (high density lipid‐cholesterol, p  = 0.01; low density lipid‐cholesterol, p  = 0.02). Levels of hs‐CRP were elevated in both children and adults, with BMI positively associated with hs‐CRP in adults with DS ( p  = 0.04). Liver enzyme values were positively associated with BMI in children and adults. The data suggest that in contrast to the general population, in individuals with Down syndrome, being overweight and obese does not appear to confer a significantly increased risk for cardiometabolic disease by biomarker profile. Individuals with DS who are overweight/obese appear to have unique cardiometabolic profiles unrelated to adiposity, notable for increased hs‐CRP and normal HA1c levels.